Leukoencephalopathy and early death associated with an Ashkenazi-Jewish founder mutation in the Hikeshi gene. Issue 2 (6th November 2015) - Edvardson, Simon; Kose, Shingo; Jalas, Chaim; Fattal-Valevski, Aviva; Watanabe, Ai; Ogawa, Yutaka; Mamada, Hiroshi; Fedick, Anastasia M; Ben-Shachar, Shay; Treff, Nathan R; Shaag, Avraham; Bale, Sherri; et al.
Abstract : Background: Leukodystrophies are genetic white matter disorders affecting the formation or maintenance of myelin. Among the recently discovered genetic defects associated with leukodystrophies, several genes converge on a common mechanism involving protein transcription/translation and ER stress response. Methods: The genetic basis of a novel congenital leukodystrophy, associated with early onset spastic paraparesis, acquired microcephaly and optic atrophy was studied in six patients from three unrelated Ashkenazi-Jewish families. To this end we used homozygosity mapping, exome analysis, western blot (Hikeshi, HSF1-pS326 and b-actin) in patient fibroblasts, indirect immunofluorescence (HSP70 and HSF1) in patient fibroblasts undergoing heat shock stress, nuclear injection of plasmids expressing Hikeshi or EGFP in patient fibroblasts, in situ hybridization and Immunoblot analysis of Hikeshi in newborn and adult mouse brain. Results: All the patients were homozygous for a missense mutation, p.Val54Leu, in C11ORF73 encoding HSP70 nuclear transporter protein, Hikeshi. The mutation segregated with the disease in the families and was carried by 1:200 Ashkenazi-Jewish individuals. The mutation was associated with undetectable level of Hikeshi in the patients' fibroblasts and with lack of nuclear HSP70 during heat shock stress, a phenomenon which was reversed upon the introduction of normal human Hikeshi to the patients cells. Hikeshi was found to be expressed in central white matter of mouse brain. Conclusions: These data underscore the importance of Hikeshi for HSP70 relocation into the nucleus. It is likely that in the absence of Hikeshi, HSP70 cannot attenuate the multiple heat shock induced nuclear phenotypes, leaving the cells unprotected during heat shock stress. We speculate that the sudden death of three of the six patients following a short febrile illness and the life-threatening myo-pericarditis in the fourth are the result of excess extra-nuclear HSP70 level which initiates cytokine release or provide target for natural killer cells. Alternatively, nuclear HSP70 might play an active role in stressed cells protection.